Vegetated roofs as a nature-based solution to mitigate climate change in a semiarid city - Robbiati, Federico Omar; Cáceres, Natalia; Barea Paci, Gustavo Javier; Ovando, Gustavo; Jim, C.Y.; Suárez, Mario Adolfo; Hick, Emmanuel Christian Bernard; Rubio, Esteban Julian; Galetto, Leonardo; Imhot, Lelia (Elsevier, 2023)
cumulating greenhouse gasses. Global warming has been related to increased carbon dioxide (CO2) emissions [1,2]. Urban areas emit a significant amount of greenhouse gasses, including 78% of total CO2 emissions [3]. Transport, the cooling and heating of buildings, industrial activities and the construction sector are the principal sources of CO2 and other emissions in urban ecosystems [4], with a significant temperature increase since the end of the last century [5]. Moreover, urbanization can remove large tracts of vegetation cover, degrade soil properties, reduce their ability to sequester and store carbon [6] and perturb biogeochemical and ecological processes [7,8]. Such changes have made the urban environment more vulnerable to climate change.Serious environmental, social and economic problems could be generated due to urban ecosystem degradation [9]. Consequently, it is urgent to develop and implement strategies to reduce atmospheric CO2 emissions in the urban context [3,10], given that urbanization has drastically intensified worldwide in recent years [6,11]. Energy production harms the environment and contributes to climate change [12,13]. Over 40% of the world’s energy is consumed in buildings [14], primarily for indoor cooling or heating [15]. The world needs to develop eco-friendly technologies to reduce building energy consumption [16]. Extensive vegetated roofs (EVRs) offer nature-based solutions that can reduce energy use, enhance energy efficiency, and inform energy-saving strategies [15,16,17]. The EVRs can contribute to this quest by reducing building energy use via multiple pathways, namely shading, insulation, increasing albedo, evapotranspiration [18–23], and suppressing the urban heat island effect [24–25]. There are several green options for carbon sequestration in urban ecosystems, including urban forests [26], turfgrass [27] and vegetated roofs [1,3]. The EVR is an innovative low-impact development practice [28] that provides notable ecosystem functions where carbon sequestration plays an important role in mitigating climate change [29]. EVRs can realize a modern biophilic technology on a building rooftop, consisting of vegetation growing on a constituted substrate [30–32]. This nature-rich technology could ameliorate various urbanization problems such as the urban heat island effect, stormwater runoff, heat stress, noise and air pollution [32–35]. EVRs are widely employed in bioclimatic architecture to complement traditional materials on flat roofs [1, 36–39]. This green technology could contribute to atmospheric carbon reduction in cities in two ways [1]. First, it directly lowers CO2 in the air by increasing carbon sequestration through photosynthesis [40–42]. Second, it indirectly depresses the building’s cooling and heating energy consumption. This passive thermal regulation is attributed to reduced ingress of solar heat in summer and reduced egress of indoor heat in winter [28,32,43,44]. Plants play an important role in atmospheric CO2 sequestration by fixing carbon into long-lived C pools via photosynthesis [45–48]. Carbon sequestration in EVRs is associated with plants, substrate, green roof structure, and management [47,29,18], especially the substrate’s organic carbon content [49]. The plant biomass in an EVR plays a crucial role in passive temperature regulation [50], mainly due to latent energy absorption during transpiration [51]. Additionally, plants can provide cooling by shading and reflecting solar and terrestrial radiant energy, reducing the mean radiant temperature, and improving ambient microclimatic conditions [52]. Based on these findings, we hypothesized that EVRs are efficient in storing CO2 and reducing emissions due to lower energy consumption. Therefore, our research objective was to assess EVR performance in the semiarid region of central Argentina by: i) quantifying the carbon sequestration capacity of EVRs and ii) estimating EVR potential to reduce CO2 emission. To quantify their carbon sequestration capacity, we calculated the total carbon storage and total carbon sequestration in three EVRs located in contrasting urban environments. To estimate the EVR potential to reduce CO2 emission, we simulated the reduction of energy consumption by the EVRs using the EnergyPlus simulation software. We adjusted the actual data of physical parameters obtained in our trials to calculate the reduction in CO2 emission. These results are essential to understanding EVR contribution to reducing CO2 emission in a semiarid region of central Argentina.